Clinical outcomes of acute kidney injury patients treated in a single-center, sub-urban satellite hospital - Mohd Nor, Fariz Safhan; Draman, Che Rosle; Seman, Mohd Ramli; Abd Manaf, Norasmiza; Abd Ghani, Azril Shahreez; Hassan, Khairul Anuar (Saudi Center for Organ Transplantation, 2015)
Acute kidney injury (AKI) is a common diagnosis among critically ill patients. Although the etiology of AKI will determine the appropriate initial management, the definitive management of established AKI is still debatable. This is a retrospective, observational, single-center analysis of a cohort of patients referred to the nephrology unit for AKI from 1st August 2010 to 31st January 2011. Those patients with indications for dialysis were treated with continuous renal replacement therapy, intermittent hemodialysis or stiff-catheter peritoneal dialysis as determined by their hemodynamic status and the technical availability of the method. The 30-day mortality rate, renal outcomes and independent prognostic factors were analyzed statistically. Seventy-five patients were reviewed. The mean age was 52.9 ± 14.5 years. Two-thirds were males and 75% were Malays. 53.3% were referred from intensive wards. Pre-renal AKI and intra-renal AKI were diagnosed in 21.3% and 73.3% patients, respectively. Sepsis was the most common cause (n = 59). The pathogens were successfully cultured in 42.3% of the cases. The median urea and creatinine were 30.4 [interquartile range (IQR) 20.3] mmol/L and 474 (IQR 398.0) µmol/L, respectively. Seventy-six percent had metabolic acidosis. Oliguria was only noted in 38.7% of the patients. Sixty percent (n = 45) of the referrals were treated with conventional, intermittent hemodialysis and 22.7% (n = 17) with continuous veno-venous hemofiltration. The 30-day mortality rate was 28%, and was higher in intensive wards (37.5% versus 17.1%). Thirty-one percent (n = 20) had complete recovery, 17 (26.6%) had partial recovery without dialysis and seven (10.9%) became dialysis dependent. The 30-day mortality rate was 28%. Referral from intensive wards was the only significant poor prognostic factor in our patients and not the dialysis modalities.